2006
DOI: 10.1007/bf02898144
|View full text |Cite
|
Sign up to set email alerts
|

Retrospectivein utero exposure assessment of PCBs using preserved umbilical cords and its application to case-control comparison

Abstract: Objectives: The aim of this study is to assess preserved umbilical cords as chemical exposure media to investigate in utero chemical exposure. Furthermore, we aim to apply preserved umbilical cords to retrospective studies of the relationship between in utero chemical exposure and neurodevelopment disorders.Methods: Two sets of preserved umbilical cord samples were analyzed for exposure to polychlorinated biphenyls (PCBs): one composed of samples from 20 healthy Japanese subjects and the other set included sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The first study reported that 17 children with ASD and 7 healthy siblings had similar concentrations of PCBs in umbilical cord samples. 139 The second study examined post-mortem brain samples and measured 7 polybrominated diphenyl ether and 7 PCB congeners; only one congener, PCB95, was associated with a genetic form of ASD (32 children with 15q11–13 duplications/deletions and other genetic syndromes) but this finding was not observed in 32 individuals with idiopathic ASD or 43 controls. 140 These two studies do not support a strong association between biomarkers of PCBs and ASD, although they are limited by small sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…The first study reported that 17 children with ASD and 7 healthy siblings had similar concentrations of PCBs in umbilical cord samples. 139 The second study examined post-mortem brain samples and measured 7 polybrominated diphenyl ether and 7 PCB congeners; only one congener, PCB95, was associated with a genetic form of ASD (32 children with 15q11–13 duplications/deletions and other genetic syndromes) but this finding was not observed in 32 individuals with idiopathic ASD or 43 controls. 140 These two studies do not support a strong association between biomarkers of PCBs and ASD, although they are limited by small sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Mitchell et al [ 26 ] examined post-mortem brain samples of children with autism and other neurodevelopmental disorders and found elevated PCB levels in brains of subjects with 15q11-q13 duplication, which is one genetic factor in autism, but not in subjects with autism of unknown aetiology. Otake and coworkers [ 27 ] compared PCB levels in preserved samples of umbilical cords from typically developing children and those with an ASC but failed to show significant differences between the two groups. However, sample sizes were very small and contamination of cord samples could not be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…• Mercury [45][46][47][48][49][50][51][52] • Air pollution [53][54][55][56][57] • Aluminum vaccine adjuvants [2,37] • Coproporphyrin [58] • Chlorpyrifos [59] • Glyphosate [60] • Phthalates [61,62] • PBDEs [63,64] • PCBs [64,65] • Electromagnetic frequencies [66] • Industrial chemical [67,68] • Acetaminophen exposure after vaccination [69][70][71][72][73] The Numerous studies have revealed that metal toxicity is increased in individuals with ASDs [74].…”
Section: • Valproic Acidmentioning
confidence: 99%